A Study on different Narrowing Processes in the Manufacturing of 1mm HTS Tapes. (September 2019) - Yao, L P; Gu, F; Yin, M Y; Li, Y Q; Song, M; Li, L; Li, Z Y
Abstract: This paper provides a reference for manufacturing the narrow HTS tapes. The narrow tapes has many advantages such as smaller AC (Alternating Current) loss and suppressed screen current compared with normal tapes. Therefore, it's meaningful to manufacture the narrow tapes. Traditionally, the way to manufacture the 1 mm HTS tapes is to use the mechanic narrowing process In this paper, we proposed two narrowing process to manufacture the 1 mm HTS (high temperature superconducting) tapes, one is using the cutting machine, the other is using the laser. The critical current tests and microscope observation tests were carried out in order to make a comparison with these two methods. Results show that the laser narrowing process has a smaller critical current loss but has dross, and the mechanical narrowing process shows a larger critical current loss but clearer section stratification.